The ascription of physical disability as a stigmatizing strategy in biblical iconic polemics - Olyan, Saul M. (The journal of Hebrew scriptures, 2009)
Physical disabilities such as blindness, lameness, muteness and deafness are sometimes ascribed to “idols” in biblical polemic as a means to devalue them. This paper explores the ascription of physical disability as one of a number of stigmatizing strategies used by biblical writers to denigrate iconic worship. I am particularly interested in what the attribution of physical disability contributes to iconic polemic that might be lacking in other stigmatizing strategies such as emphasizing the material or manufactured nature of “idols.”